2013
DOI: 10.1155/2013/468043
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rabies Antigen in the Saliva and Brains of Apparently Healthy Dogs Slaughtered for Human Consumption and Its Public Health Implications in Abia State, Nigeria

Abstract: The study was carried out in eight dogs slaughtering outlets within four Local Government Areas of the State for the determination of rabies antigen in the saliva and brain of apparently healthy dogs slaughtered for human consumption. A total of one hundred (100) samples each of saliva and brain were collected before and after slaughter, respectively, between April to June, 2013, in the selected areas. The saliva was subjected to rapid immune-chromatographic test (RICT) while direct fluorescent antibody test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 8 publications
4
46
1
1
Order By: Relevance
“…The domestic dog is a major reservoir and vector of human rabies in Nigeria, accounting for nearly 99% of human rabies exposures (Adeyemi, Adetunji, James, & Alonge, ; Ameh, Dzikwi, & Umoh, ; Mshelbwala, Ogunkoya, & Maikai, ; Otolorin, Dzikwi, Umoh, Mshelbwala, & Danjuma, ). The risk and rate of canine rabies transmission depend on many factors, including the density of the dog population and their social behaviour (Oboegbulem & Nwakonobi, ; Hambolu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The domestic dog is a major reservoir and vector of human rabies in Nigeria, accounting for nearly 99% of human rabies exposures (Adeyemi, Adetunji, James, & Alonge, ; Ameh, Dzikwi, & Umoh, ; Mshelbwala, Ogunkoya, & Maikai, ; Otolorin, Dzikwi, Umoh, Mshelbwala, & Danjuma, ). The risk and rate of canine rabies transmission depend on many factors, including the density of the dog population and their social behaviour (Oboegbulem & Nwakonobi, ; Hambolu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, instead of the recommended approach to euthanasia and testing of the dog, it was killed by the public and used for a traditional treatment . Dog meat is consumed for various reasons, notably for its medicinal potency, as an aphrodisiac, its taste and as protection against attack by evil spirits and rabies . The processing of the rabid dog serves as a potential source of infection to those involved in the act, because nervous tissues and fluid from the infected dog are potential source of infection .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Dog meat is consumed for various reasons, notably for its medicinal potency, as an aphrodisiac, its taste and as protection against attack by evil spirits and rabies. 5,7 The processing of the rabid dog serves as a potential source of infection to those involved in the act, because nervous tissues and fluid from the infected dog are potential source of infection. 5,8 This response results in an ineffective approach to rabies prevention while also posing additional risks to people who catch, kill, and butcher the dog.…”
Section: Discussionmentioning
confidence: 99%
“…However, few reports in cats have been documented from the records of National Veterinary Research Institute, Vom (Ogunkoya [13] making the role of cats in the epidemiology of the disease negligible. Recently, Mshelbwala et al [9] reported dog bite to be the major route by which humans contact the disease in Abia State, Nigeria. They were of the opinion that majority of the offending dogs were not vaccinated against the disease, but if previously vaccinated, owners fail to revaccinate following expiration of previous vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mshelbwala et al [8], Mshelbwala et al [9] and Hambolu et al [10] have reported that the prevalence of the disease is still on the rise. The disease is caused by a virus of the family Rhabdoviridae and genus Lyssavirus , now called lyssa virus 1 (RABV gen1).…”
Section: Introductionmentioning
confidence: 99%